Advertising with priming effect to improve the mastery of vision and mission of a lambayecana educational institution, 2019. - Suárez Luna, Julio César (2018)
The research arises from the need to demonstrate that advertising with a priming effect can improve the domain of the vision and mission of an educational institution in students ofbasic education, specifically in their conceptions of social projection, environmental care and humanistic learning. Its objective was to determine the effects of priming in advertisingaimed at improving the domain of institutional purposes. The design was experimental, and the population, students of the VII cycle of EBR. The techniques used were the observationrecord and the survey, and descriptive statistics for information processing. The results show that advertising with a priming effect improves vision mastery, 25% more in the experimentalgroup than in the control group, and regarding the mission of the institution, the level of mastery is maintained.